What is the shareholder wealth impact of target CEO retention in private equity deals? - Bargeron, Leonce L.; Schlingemann, Frederik P.; Stulz, René M.; Zutter, Chad J. (Journal of Corporate Finance, 2017)
There is a widespread belief among observers that a lower premium is paid when the target CEO is retained by the acquirer in a private equity deal because conflicts of interest lead her to negotiate less aggressively on behalf of the target shareholders. Our empirical evidence is not consistent with this belief. We find that, when a private equity acquirer retains the target CEO, target shareholders receive an acquisition premium that is larger by as much as 18% of pre-acquisition firm value when accounting for the endogeneity of the retention decision. Our evidence is consistent with what we call the “valuable CEO hypothesis.” With this hypothesis, retention of the CEO can be valuable to private equity acquirers because, unlike public operating companies with managers in place, these acquirers have to find a CEO to run the post-acquisition company and the incumbent CEO may be the best choice to do so because she has valuable firm-specific human capital. When a private equity acquirer finds a target with a CEO who can manage the post-acquisition company better than other potential CEOs, we expect target shareholders to receive a larger premium because the post-acquisition value of the target is higher.